Does using action-oriented language increase men’s preferences for psychological therapies? - Boeles Rowland, Essie (2020)
Background: Men seek help less than women for mental health difficulties and increasing emphasis has been placed on services becoming ‘male-friendly’ to increase men’s uptake. However, many extant ‘male-friendly’ recommendations lack an empirical basis. The current study evaluates one such recommendation, using ‘action-oriented’ language, to explore (a) whether men prefer therapies described using action-oriented language and (b) whether preferences are associated with masculinities or psychological distress.